2013
DOI: 10.1177/1077546313505124
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of torsional wave in a composite layer overlying an anisotropic heterogeneous half-space with initial stress

Abstract: In this paper we have discussed the propagation of torsional wave in a composite layer overlying an anisotropic heterogeneous half space with initial stress. The method of separation of variables is applied to find the dispersion equation. Numerical results analyzing the dispersion equation are discussed and presented by means of graphs. The effect of reinforcement, inhomogeneity parameter and the initial stress on the propagation of torsional surface wave is the main objective in our study. It has been observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Chattopadhyay et al [22] also shown that heterogeneous anisotropic half space with initial stress allow torsional wave to propagate. Recently Dhua et al [23] discussed the effect of heterogeneity, initial stress and reinforcement on the propagation of torsional surface wave in a composite layer overlying an anisotropic heterogeneous half space. Dhua et al [24] also studied the propagation of surface wave in a fluid layer overlying a slightly compressible, finitely deformed elastic medium.…”
Section: Introductionmentioning
confidence: 99%
“…Chattopadhyay et al [22] also shown that heterogeneous anisotropic half space with initial stress allow torsional wave to propagate. Recently Dhua et al [23] discussed the effect of heterogeneity, initial stress and reinforcement on the propagation of torsional surface wave in a composite layer overlying an anisotropic heterogeneous half space. Dhua et al [24] also studied the propagation of surface wave in a fluid layer overlying a slightly compressible, finitely deformed elastic medium.…”
Section: Introductionmentioning
confidence: 99%
“…Biot (1940) described the vital effect of the initial stress on propagation of seismic waves. A brief discussion on the upshot of the initial stress on the torsional wave propagation was explored by Dhua et al (2015). Gupta and Bhengra (2017b) gave an extensive discussion regarding the favor of the initial stress on the soil dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Othman and Song [15] have studied the effects of thermal parameters on the reflection of plane waves from a solid half-space. The effect of initial stress on a torsional wave is discussed by Dhua et al [16], whereas Chatterjee et al [17] have studied in detail the effect on reflected quasi-P and quasi-SV waves. Very recently, Majhi et al [18] investigated the reflection and transmission of plane SH-waves in two semi-infinite anisotropic magnetoelastic media.…”
Section: Introductionmentioning
confidence: 99%